Two- and three-photon double ionization of helium by soft x-ray free-electron laser pulses. (5th March 2019) - Shimada, Hiroyuki; Komatsu, Kazma; Komatsubara, Wataru; Mizuno, Tomoya; Miyake, Soichiro; Minemoto, Shinichirou; Sakai, Hirofumi; Majima, Takuya; Owada, Shigeki; Togashi, Tadashi; Yabashi, Makina; Yagishita, Akira
Abstract: The multiphoton double ionization of He was investigated using a soft x-ray free-electron laser (SX-FEL), in the perturbative intensity regime (<10 13 W cm −2 ). The photon energy was tuned to the transition between the 1s and 2p levels of He + ions. At this resonance energy of 40.8 eV, both sequential three-photon double ionization (S3PDI) and two-photon double ionization (2PDI) were measured by electron spectroscopy and by ion time-of-flight mass spectroscopy. We distinguished S3PDI from 2PDI by electron spectroscopy. Based on these experimental data, SX-FEL pulse-energy dependences of electron and ion yields for both S3PDI and 2PDI were discussed. The angular distribution of 2p photoelectrons emitted from He + (2p) ions in the S3PDI process was examined as an example of the simplest photoemission dynamics.